Pump Stations of Water Reservoirs (Texas Journal of Multidisciplinary Studies, 2022)
Normal stagnation level (NSL) is such that when the reservoir is filled to that level, the dam can hold the accumulated water in it for a long time without damage. The accuracy and duration of the normal stagnation level depend on the flow regime of the river and its level of management. Normal stagnation is achieved annually in the river management, and in other perennials only in the year when there is a lot of water